2022
DOI: 10.1155/2022/1418232
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of Endometrial Carcinoma ceRNA Network and Screening of Key Genes Based on TCGA Database

Abstract: Objective. Long noncoding RNA (lncRNA) has received more and more attention in human tumor research. This study is aimed at clarifying the regulatory network of lncRNAs-microRNAs- (miRNAs-) mRNAs and at determining the relevant targets in the development of endometrial cancers. Methods. Download the miRNA, mRNA, and lncRNA expression profile data of endometrial cancer patients from TCGA; use the “DESeq2” package of R software to identify the differential expression of miRNAs, mRNAs, and lncRNAs; construct a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This work allowed identifying tens of these axes, with six of them carrying a high prognostic value. In the same year, Song and collaborators also took advantage of TGCA database to reconstruct a ceRNET including 5 deregulated lncRNA, 7 deregulated miR, and 90 deregulated mRNA [69]. In Figure 1, we report two simplified examples of ceRNET in EC.…”
Section: Role Of Circulating Mirna In Ec: Mir Cernet and Cancer Biologymentioning
confidence: 99%
“…This work allowed identifying tens of these axes, with six of them carrying a high prognostic value. In the same year, Song and collaborators also took advantage of TGCA database to reconstruct a ceRNET including 5 deregulated lncRNA, 7 deregulated miR, and 90 deregulated mRNA [69]. In Figure 1, we report two simplified examples of ceRNET in EC.…”
Section: Role Of Circulating Mirna In Ec: Mir Cernet and Cancer Biologymentioning
confidence: 99%
“…This network identifies 169 prognosis-associated RNAs, including 92 lncRNAs, 16 miRNAs, and 61 mRNAs (194). Several genes, such as ADRA1A, ANGPTL1, FBXO32, KCNMA1, DCN, LEFTY1, LIN28A, LHX3, ST8SIA3, and CEP55, are also regulated by the lncRNA-miRNA-mRNA network (195). Moreover, miRNA-mRNA regulatory networks are linked to the biological process of negative regulation of transcription from the RNA polymerase II promoter and positive regulation from the RNAD promoter (166).…”
Section: Mirna and Ecmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%